2014
DOI: 10.1021/jp503916e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modification with Vanadium or Carbon on Destructive Sorption of Halocarbons over Nanocrystalline MgO: The Role of Active Sites in Initiation of the Solid-State Reaction

Abstract: Small amounts of vanadium or carbon added to nanocrystalline MgO aerogels were shown to promote their activity in destructive sorption of CF2Cl2 and CFCl3 halocarbons. This reaction is characterized by a prolonged induction period, which is considerably shortened after the addition of the studied promoters. It was demonstrated that the promoting effect of finely dispersed carbon did not depend on its location relative to the MgO nanoparticles. Approximately the same results were obtained when carbon was deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…For instance, nanocrystalline mesoporous oxides with nanoparticle sizes under 10 nm oen have unusually high reactivity in many chemical reactions. This property leads to their use as efficient catalysts [1][2][3] and destructive sorbents [4][5][6][7][8][9][10] for the neutralization of various toxic compounds. However, the products resulting from their solidstate reactions are usually not nanocrystalline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, nanocrystalline mesoporous oxides with nanoparticle sizes under 10 nm oen have unusually high reactivity in many chemical reactions. This property leads to their use as efficient catalysts [1][2][3] and destructive sorbents [4][5][6][7][8][9][10] for the neutralization of various toxic compounds. However, the products resulting from their solidstate reactions are usually not nanocrystalline.…”
Section: Introductionmentioning
confidence: 99%
“…19,23 Earlier we have reported that the carbon coating deposited on the surface of the oxide nanoparticles can act as a nanoreactor shell. On the one hand, such coating can be penetrable for the reactant molecules from the gas 7,10,24,25 or liquid 26 phases making it possible to initiate various catalytic or solid-state reactions inside the nanoreactor. Moreover, the carbon coating prevents sintering of nanoparticles inside the shell during the temperature increase and stabilizes their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…Klabunde et al have done a lot of research on the synthesis and application of magnesium oxide. For example, they were investigated the effect of the crystallites of magnesium oxide on the catalytic performance and the effect of vanadium and carbon doping on the adsorption properties of magnesium oxide [18,19]. Using SBA-15 and CMK-3 as hard template, mesoporous MgO was synthesized in Tiemann's report [20].…”
Section: Introductionmentioning
confidence: 99%
“…32,54,55 A strong signal of TNB radical anions characterized by anisotropic splitting on a nitrogen atom with A zz = 27.2 G was observed on the AP-MgO sample after activation in nitrogen flow without any reaction. 56 Its intensity on activated AP-MgO before reaction was about 6×10 18 g -1 . The concentration of electrondonor sites gradually decreased during reaction with CF 2 Cl 2 (Fig.…”
Section: Characterization Of Electron-donor and Electron-acceptor Sitmentioning
confidence: 96%